2015
DOI: 10.1053/j.gastro.2015.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing Colonoscopy Screening for Elderly Individuals Based on Screening History, Cancer Risk, and Comorbidity Status Could Increase Cost Effectiveness

Abstract: Background & Aims Colorectal cancer (CRC) screening decisions for elderly individuals are often made based primarily on age—other factors that affect the effectiveness and cost effectiveness of screening are often not considered. We investigated the relative importance of factors that could be used to identify those elderly individuals most likely to benefit from CRC screening and determined the maximum ages at which screening remains cost effective based on these factors. Methods We used a microsimulation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 47 publications
3
77
0
Order By: Relevance
“…van Hees' team also reported that fewer co-morbidities were associated with screening at older ages. 19 Lansdorp-Vogelaar et al 20 and Gross et al 21 whose studies are included in this review, also arrived at a similar conclusion.…”
Section: Colorectal Cancer Screeningsupporting
confidence: 72%
See 1 more Smart Citation
“…van Hees' team also reported that fewer co-morbidities were associated with screening at older ages. 19 Lansdorp-Vogelaar et al 20 and Gross et al 21 whose studies are included in this review, also arrived at a similar conclusion.…”
Section: Colorectal Cancer Screeningsupporting
confidence: 72%
“…A summary of the literature review of screening for colorectal cancer is shown in Table 1. [11][12][13][14][15][16][17][18][19][20][21][22]27 Hong Kong Med J ⎥ Volume 23 Number 5 ⎥ October 2017 ⎥ www.hkmj.org To quantify the effect of screening colonoscopy on prevention, early detection, and overdiagnosis in the last 10 years (As above) Colonoscopies had the advantages of prevention and early detection, with a low risk of over-diagnosis; 180 000 colorectal cancers are estimated to have been prevented (97% were prevented by screening colonoscopies done up to age 75 years); 1/121 screening colonoscopies were early detected up to age 80 years (89% by screening colonoscopies up to age 75 years); over-diagnosed in 1/1089 screening colonoscopies (58% arose from screening colonoscopies done on those age >70 years)…”
Section: Colorectal Cancer Screeningmentioning
confidence: 99%
“…Carcinoembryonic antigen and cancer antigen 19-9 are widely used biomarkers for CRC diagnosis. Endoscopy and blood screening have been proved to effectively reduce the incidence and mortality of CRC (3). However, the prognosis of CRC patients remains poor, with a 50-59% 5-year survival rate (2).…”
Section: Introductionmentioning
confidence: 99%
“…van Hees et al ,1 tackled these questions for the elderly by modelling expected costs and benefits of colonoscopy for a multitude of groups characterised by specific combinations of risk factors including age, sex, race, personal characteristics, lifestyle factors, screening history and comorbidities. For each group they estimated: expected number of quality adjusted life years due to ill health from adverse events, colorectal cancer diagnoses and deaths; expected financial costs to those screened due to out-of-pocket expenses/lost income because of screening, treatment and comorbidities; and ratio of these two as a measure of cost-effectiveness.…”
Section: Methodsmentioning
confidence: 99%